Carbon farming training and welfare: Evidence from Northern Ghana - Charles Yaw Okyere; Lukas Kornher (University of Bonn, Center for Development Research (ZEF), 2022)
Carbon farming, particularly soil carbon climate strategies, has emerged as a popular tool in addressing climate change and variability in worldwide agriculture. Yet, there is a paucity of evidence on its application, and even more so, limited evidence exists on the welfare impacts in developing countries, where the negative impacts of climate change and variability remain disproportionately higher. This paper presents the results of a study on biochar and compost production training and its welfare effects on farm households in Northern Ghana using doubly robust estimators. We find that the intervention had statistically significant positive effects on agricultural productivity and welfare outcomes. The results show the prospect of using soil carbon climate strategies in improving the welfare of farm households in developing countries.
Keywords: Q12; Q15; Q16; Q18; Q57; C21; I31; I32; 330; Climate-smart Agriculture; Carbon Farming; Biochar; Compost; Welfare; Poverty; Northern Ghana